2015
DOI: 10.1111/bor.12113
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution and variability of atmospheric freeze/thaw cycles in Norway over the last six decades (1950–2013)

Abstract: This study focused on atmospheric freeze/thaw cycles in Norway and presents the results of processing daily thermal data from 20 Norwegian meteorological stations for the period 1950–2013. Its two major aims were: (i) to provide long‐term time series of atmospheric freeze/thaw cycle data for Norway, and (ii) to analyse their trends over the last six decades. The study highlights the spatial and temporal modalities of the distribution of freeze/thaw cycles in Norway. The differences in the seasonal distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Here, we use zero crossings based on air temperature as a proxy for slippery conditions. A zero crossing is defined as T min < 0 and T max > 0 on the same day (Geiger et al, 2007;Kerguillec, 2015). Although zero crossings calculated from 2 m air temperature do not coincide perfectly with slippery conditions, they have the advantage of being available for the future period at 1 km resolution, as opposed to road temperature and dew point temperature and humidity.…”
Section: Climate Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we use zero crossings based on air temperature as a proxy for slippery conditions. A zero crossing is defined as T min < 0 and T max > 0 on the same day (Geiger et al, 2007;Kerguillec, 2015). Although zero crossings calculated from 2 m air temperature do not coincide perfectly with slippery conditions, they have the advantage of being available for the future period at 1 km resolution, as opposed to road temperature and dew point temperature and humidity.…”
Section: Climate Indicesmentioning
confidence: 99%
“…Trends are, however, sensitive to the choice of period. This is shown by Kerguillec (2015), who studied zero crossings in Norway using daily thermal data from 20 meteorological stations for the period 1950-2013, including two stations in Troms. For these two stations, the frequency of zero crossings increased during the periods 1970-1979and 1990-1999but decreased in the 1980s.…”
Section: Zero Crossingsmentioning
confidence: 99%
“…Trends are, however, very sensitive to the choice of period.. This is clearly shown by Kerguillec (2015), who studied atmospheric freeze/thaw cycles (zero-crossings) in Norway using daily thermal data from 20 meteorological stations for the period 1950-2013. Different decades displayed different trend directions and magnitudes at the different stations.…”
Section: Future Developmentmentioning
confidence: 99%
“…The topic of this study is, however, zero-crossings of the two-metre air temperature. Kerguillec (2015) studied historical trends and variability in annual and seasonal numbers of DZCs for 20 weather stations in Norway during the period 1950-2013. He concluded that, because DZCs are most frequent in months with the mean temperature close to 0 C, both the average number of such crossings and the trends during different decades differ with altitude, latitude and distance from the coast.…”
Section: Introductionmentioning
confidence: 99%
“…They used the number of days with mean temperature from −1.5 to +1.0 C as a proxy for the number of DZCs. Neither Kerguillec (2015) nor Dyrrdal et al (2011) included climate projections. Miles et al (2011) estimated changes in the frequencies of DZCs in different seasons up to 2050, based on a 4-member ensemble of climate models under the A1B emission scenario.…”
Section: Introductionmentioning
confidence: 99%